Practical model-based systems engineering - Fernández Pérez, José Luis; Hernandez, Carlos (Artech House technology management and professional development library., 2019)
For systems engineers and practitioners, this book provides the analytic, design and modeling tools of the Model Based Systems Engineering (MBSE) methodology of Integrated Systems Engineering (ISE) and Pipelines of Processes in Object Oriented Architectures (PPOOA) methodology. --